2013
DOI: 10.1007/s10006-013-0413-6
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic assistance in the diagnosis and treatmentof odontogenic maxillary sinus disease

Abstract: Endoscopy of the maxillary sinus can be applied in a variety of indications. Alone or in combination with conventional surgery, it is a minimally invasive and highly diagnostic tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
0
7
0
2
Order By: Relevance
“…Forty-nine studies reported specific diagnostic criteria 7,10,1662 and 14 studies did not report any diagnostic criteria (either original or referenced) for OS. 8,11,6374 It should be noted that four articles 10,21,31,39 were retrospective radiological analyses and provided radiologic diagnostic criteria only. Figure 1 reports a graphical analysis of the 63 included articles in terms of their overall use of diagnostic criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Forty-nine studies reported specific diagnostic criteria 7,10,1662 and 14 studies did not report any diagnostic criteria (either original or referenced) for OS. 8,11,6374 It should be noted that four articles 10,21,31,39 were retrospective radiological analyses and provided radiologic diagnostic criteria only. Figure 1 reports a graphical analysis of the 63 included articles in terms of their overall use of diagnostic criteria.…”
Section: Resultsmentioning
confidence: 99%
“…To further highlight the need for complete scans, we might consider that an endoscopic sinus surgery procedure is not only advisable, but more correctly required in almost all patients that need surgical treatment of a SCDDT . Due to the frequent extramaxillary involvement we report in this article, both old and new techniques for SCDDT patients, such as the Caldwell‐Luc procedure, double‐barrel access, bony window access, and antral retriever, which focus on the maxillary sinus alone, should be used only in the few select patients in which the condition is truly limited to the maxillary sinus and/or belonging to class 2c (implant dislocation with no sinusitis).…”
Section: Discussionmentioning
confidence: 99%
“…Cabe mencionar que varios casos tratados con esta técnica han sido sometidos a un nuevo procedimiento quirúrgico, siendo el abordaje externo, el tratamiento de elección , como menciona Venetis et al, que informa que entre el 10 y el 15% de los pacientes que se someten a la técnica endoscópica del seno, requirieron una cirugía de revisión, incluso no está claro si la cirugía endoscópica repara la función mucociliar en la mucosa del seno maxilar enfermo (23) . La literatura describe una técnica que combina a los dos tratamientos en cuestión, permitiendo una mejor visualización y exploración al interior del seno maxilar, eliminación de la infección existente y de pólipos, además, logra la permeabilidad natural del ostium del seno maxilar (24) .…”
Section: Discussionunclassified